OPTIMIZATION OF DIGITAL RECRUITMENT THROUGH JOBSTREET: CASE STUDY AT PT. MEGA SMART PERSADA - A. Putri Djohar Tenri Waru (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Information openness supported by internet access provides a new strategy for companies in conducting recruitment processes using online recruitment systems such as JobStreet. This research aims to analyse and explore the recruitment process, explore the obstacles and provide recommendations to improve the effectiveness of recruitment using JobStreet application. By using qualitative methods, data collection techniques are in-depth interviews, observation and document analysis. The results showed that PT Mega Smart Persada uses JobStreet in advertising job vacancies and finding the best candidates, but its use has not maximised the existing features. so it is recommended that the recruitment team maximise the job ad performance traker and automatic screening features, as well as conduct training to the recruitment team so that the recruitment process is effective, efficient to get candidates that match the classification.